Curcumin administration alleviates seminal vesicle damage in type 1 diabetic rats by promoting AQP8 expression through AR activation - Dawei Ni; Kun Liu; Ning Wu; Bin You; Baibing Yang; Wei Wu; Yutian Dai (Scientific Reports)
Abstract Diabetes is a detriment to male reproductive health, notably through its capacity to diminish secretion from accessory glands such as the seminal vesicles and prostate, which are crucial for reproductive function. Curcumin, a naturally derived polyphenol renowned for its anti-inflammatory and antioxidative attributes, has demonstrated potential in mitigating tissue damage across various organs in diabetic patients. Despite its established benefits, the specific impact of curcumin on seminal vesicle damage in the context of diabetes remains underexplored. This investigation delves into the therapeutic potential of curcumin in ameliorating seminal vesicle damage in diabetic rats, thereby elucidating its underlying mechanisms. This study focused on twenty male SD rats divided into two distinct groups, a control cohort and a diabetic contingent, and employed a streptozocin (STZ)-induced type 1 diabetic rat model to ascertain seminal vesicle alterations secondary to diabetes. Ultrasonography was used to measure rat seminal vesicle sizes for comparison with postdissection measurements. This study revealed that (1) seminal vesicle volume and seminal fluid secretion were reduced in diabetic rats and (2) ultrasonography can predict seminal vesicle secretory dysfunction in diabetic rats, providing a theoretical basis for selecting animal models of diabetic seminal vesicle dysfunction for subsequent studies. Thirty male SD rats were subsequently divided into three groups: control, diabetic, and curcumin-treated. The curcumin group, which was subjected to a one-month-long intervention after STZ-induced diabetes onset, exhibited significant histological and functional recovery. Haematoxylin‒eosin (HE) staining revealed disordered seminal vesicle tissue structures and decreased epithelial cell height in diabetic rats, which was partially restored after curcumin treatment. Western blot and PCR results demonstrated that the expression levels of androgen receptor (AR) and aquaporin (AQP)8 in the seminal vesicle tissues of diabetic rats were decreased, whereas curcumin treatment led to increases in the expression levels of AR and AQP8. Seminal vesicle cells were cultured in vitro and divided into six groups: control, HG, HG-CUR-5 µM, HG-CUR-10 µM, HG-CUR-20 µM, and HG-CUR-50 µM. After 48 h of intervention, the fructose concentration in the culture medium was measured, and the expression of AR and AQP8 in the control, HG, and HG-CUR-20 µM groups was determined via Western blotting and PCR. The results revealed that the expression of AR and APQ8 in high glucose-treated seminal vesicle cells was decreased and that curcumin treatment upregulated the expression of AR and AQP8. After the addition of bicalutamide (an AR inhibitor), the expression of AQP8 was reduced. These findings suggest that curcumin may alleviate seminal vesicle damage in type 1 diabetic rats by activating the AR-AQP8 pathway.